Designing Basic Variables as Linguistic States with Multiple Channel Queueing Models and Supply Priorities In Uncertainty Environment - Mueen, Zeina (Research India Publications, 2016)
This paper develops a new contribution for constructing an architecture that describes the linguistic states as intervals with two basic variables; arrival rates and service rates, while increasing the supplying order of demands in the manufacturing production line under uncertainty environment. The basic idea for this paper considers classifying these basic values as linguistic values represented by three ranges for each value, in a multiple channel queueing model with two class of priority having ranges in each interval. Trapezoidal fuzzy numbers are considered as they are efficient to build these intervals. Adopting robust ranking index and a-cut confidence interval are suitable approaches for converting the fuzzy arrival and service values into crisp values. Numerical application is shown for the application of this new approach in evaluating the exact real waiting time of customers in the queue for each interval, which further contributes to evaluation of the whole system in uncertainty environment. Hence, an easy way for dealing with fuzzy numbers in decision-making problems is developed